Mental health in senior housing: racial/ethnic patterns and correlates of major depressive disorder. - Robison, Julie; Schensul, Jean J; Coman, Emil; Diefenbach, Gretchen J; Radda, Kim E; Gaztambide, Sonia; Disch, William B (Aging & mental health, 2009)
Mental health problems are associated with disability, overuse of medical care, higher rates of mortality and suicide as well as personal suffering for older adults. Residents of urban, low-income senior housing may face increased risk of a variety of mental health problems, including depression. This study identified the prevalence of multiple mental health problems in older residents of low-income senior housing and explored correlates of major depressive disorder for the two largest ethnic groups: black and Latino.
Keywords: African Americans; Age Distribution; Aged; Connecticut; Depressive Disorder, Major; Female; Geriatric Assessment; Hispanic Americans; Housing for the Elderly; Humans; Interview, Psychological; Leisure Activities; Male; Mental Disorders; Mental Health; Middle Aged; Poverty; Prevalence; Psychiatric Status Rating Scales; Psychometrics; Stress, Psychological; Urban Population